2015
DOI: 10.1128/jvi.01610-15
|View full text |Cite
|
Sign up to set email alerts
|

CD8lowCD100T Cells Identify a Novel CD8 T Cell Subset Associated with Viral Control during Human Hantaan Virus Infection

Abstract: Hantaan virus (HTNV) infection can cause a severe lethal hemorrhagic fever with renal syndrome (HFRS) in humans. CD8؉ T cells play a critical role in combating HTNV infections. However, the contributions of different CD8 ؉ T cell subsets to the immune response against viral infection are poorly understood. Here, we identified a novel subset of CD8 CD8 T cells play a critical role in combating viral infections. Dramatic cellular changes occur as T cells transition through the following three characteristic pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…We performed neutrophil chemotaxis assays (CXCL8 ligand, 0, 30, 300 ng/ml) in the presence or absence of BKM120 ( 0–1000nM) and as expected from our prior work, the migration of neutrophils isolated from mouse bone marrow was not significantly affected by PI3K inhibition (Figure 1 E) [33, 34]. To determine how BKM120 treatment affected tumor cell migration and invasion, we performed in vitro transwell invasion assays.…”
Section: Resultsmentioning
confidence: 68%
“…We performed neutrophil chemotaxis assays (CXCL8 ligand, 0, 30, 300 ng/ml) in the presence or absence of BKM120 ( 0–1000nM) and as expected from our prior work, the migration of neutrophils isolated from mouse bone marrow was not significantly affected by PI3K inhibition (Figure 1 E) [33, 34]. To determine how BKM120 treatment affected tumor cell migration and invasion, we performed in vitro transwell invasion assays.…”
Section: Resultsmentioning
confidence: 68%
“…In fact, some studies have shown that a proportion of CD8 + T cells displays low surface expression of the CD8 molecule after viral infections [27][28][29]. During the early phase of human Hantaan virus (HTNV) infection, CD8 low cells expressed high levels of cytolytic effector molecules and were associated with high activation status, exhibiting an effector phenotype as CCR7 +/-CD45RA -CD127 high CD27 int CD28 low CD62L low [30]. This study also revealed these cells as the main producers of IFN-γ and TNF among CD8 + T cells, when stimulated with specific HTNV peptides.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Other investigators detected increased amounts of PD-L1 in hantavirus-infected cultures of rat endothelial cells (80). In HFRS patients, hantavirus-induced PD-L1 may be responsible for the contraction of a newly identified highly cytotoxic T cell subset that strongly upregulates PD-1 in the late phase of hantavirus infection (81). Hantavirus-induced expression of PD-L1 and PD-L2 may contribute to the recently described protection of hantavirus-infected endothelial cells from cytotoxic attack by CD8+ T cells and NK cells (82).…”
Section: Discussionmentioning
confidence: 99%